Drug Resistance in Non-Small Cell Lung Cancer: A Potential for NOTCH Targeting? - Sosa Iglesias, Venus; Giuranno, Lorena; Dubois, Ludwig J.; Theys, Jan; Vooijs, Marc (Frontiers in Oncology, 2018)
Drug resistance is a major cause for therapeutic failure in non-small cell lung cancer (NSCLC) leading to tumor recurrence, and disease progression. Cell intrinsic mechanisms of resistance include changes in the expression of drug transporters, activation of pro-survival and anti-apoptotic pathways, as well non-intrinsic influences of the tumor microenvironment. It has become evident that tumors are composed of a heterogeneous population of cells with different genetic, epigenetic, and phenotypic characteristics that results in diverse responses to therapy and underlies the emergence of resistant clones. This tumor heterogeneity is driven by subpopulations of tumor cells termed cancer stem cells (CSCs) that have tumor initiating capabilities, are highly self-renewing, and retain the ability for multi-lineage differentiation. CSCs have been identified in NSCLC and have been associated with chemo- and radiotherapy resistance. Stem cell pathways are frequently deregulated in cancer and are implicated in recurrence after treatment. Here we focus on the Notch signaling pathway, which has a role in stem cell maintenance, in non-squamous non-small lung cancer, and we critically assess the potential for targeting the Notch pathway to overcome resistance to chemotherapeutic and targeted agents using both preclinical and clinical evidence.